A 2D Layered Lanthanide Hydroxide Showing Slow Relaxation of Magnetization – Dy8(OH)20Cl4·6H2O. Issue 29 (1st October 2013) - Monteiro, Bernardo; Pereira, Cláudia C. L.; Coutinho, Joana T.; Pereira, Laura C. J.; Marçalo, Joaquim; Almeida, Manuel
Abstract: Invited for the cover of this issue is the group of Manuel Almeida at the University of Lisbon. The cover image illustrates the unit cell of a layered dysprosium hydroxide material that is the first example of a layered lanthanide compound showing single‐molecule‐magnet behavior. Abstract : Our studies show single‐molecule‐magnet (SMM) behavior for the first time in a layered lanthanide compound... Read more about the story behind the cover in theCover Profile and about the research itself onp. 5059 ff .